Confirmation of parity violation in the gamma decay of Hf-180(m) - Stone, JR; Goldring, G; Stone, N; Severijns, N; Hass, M; Zakoucky, D; Giles, T; Koester, U; Kraev, I; Lakshmi, S; Lindroos, M; Wauters, F (2007)
This paper reports measurements made using the technique of online nuclear orientation which reexamine the γ decay of isomeric 180Hfm and specifically the 501 keV 8 - 6+ transition. The irregular admixture of E2 to M2/E3 multipolarity in this transition, deduced from the forward-backward asymmetry of its angular distribution, has for decades stood as the prime evidence for parity mixing in nuclear states. The experiment, based on ion implantation of the newly developed mass-separated 180Hfm beam at the CERN online isotope mass separator (ISOLDE) facility into an iron foil maintained at millikelvin temperatures, produces higher degrees of polarization than were achieved in previous studies of this system. The value found for the E2/M2 mixing ratio, ε=-0.0324(16)(19), is in close agreement with the previous published average value ε=-0.030(2), in full confirmation of the presence of the irregular E2 admixture in the 501 keV transition. The temperature dependence of the forward-backward asymmetry has been measured over a more extended range of nuclear polarization than previously possible, giving further evidence for parity mixing of the 8- and 8+ levels and the deduced E2/M2 mixing ratio. © 2007 The American Physical Society.